Growing up in heaven : the eternal connection between parent and child - Van Praagh, James (New York : HarperOne, 2011)
"Blessed with an extraordinary gift, James Van Praagh has the rare ability to bridge the gap between this world and the next. Based on nearly thirty years of spirit communication, this world-famous medium takes us on a powerful, emotional and ultimately inspiring journey to life on the other side. In Growing Up In Heaven, he provides solace and insight by offering us a remarkably detailed portrayal of a child's soul on its journey from this world to the next. Through true stories and messages from those who have passed on, we experience the unbreakable bond between parent and child while glimpsing an amazing vision of heaven. Opening our eyes and hearts to the reality that love transcends the physical and material planes of this world, Growing Up In Heaven has the ability to heal wounds by lifting our spirits with the knowledge that our departed ones will always be a part of our lives"--
Pt. 1. Crossing over. When a child transitions ; A child arrives in spirit ; A child's life in spirit -- pt. 2. The soul's make-up. The soul ; Soul lessons ; The soul returns -- pt. 3. Healing your life. Spirit signposts ; Moving on ; Letters from Heaven -- A step in time.
100258
Keywords: Spiritualism; Parent and child; Parent-child relationship